RNA Sequencing-Based Total RNA Profiling; The Oncogenic MiR-191 Identification as a Novel Biomarker for Breast Cancer - Majed, Sevan Omer (Cellular and Molecular Biology, 2022)
This study aims to screen the differential expression of total RNA transcripts in formalin-fixed paraffin-embedded tissues (FFPETs) in breast cancer (BRCA) and normal adjacent tissues (NATs) and identify miR-191 as a new biomarker for early diagnosing BRCA. Differentially expressed genes (DEGs) by MACE-Seq and differentially expressed ncRNAs (DEncRNAs) by the TrueQuant technique were examined in this study. The miR-191 expression level was measured by Real Time-qPCR. An average of 4,739 coding genes from 25,713 significantly down-regulated genes was identified, whereas 3,954 coding genes were significantly up-regulated in the BRCA against NAT. An average of 1450 ncRNAs, including up-regulated= 679 and down-regulated= 780, were differentially expressed in 7 paired samples of BRCA and NAT. Among the ncRNAs, 227 microRNAs, including unchanged= 152, down=53, and up=22, were differentially expressed. MiR-191 was one of the 22 significant up-regulation, with p=0.0001. RT-qPCR results confirmed that miR-191, p=0.003, was significantly over-expressed in 120 paired samples of BRCA and NAT. Furthermore, NextSeq 500 revealed that a single nucleotide polymorphism (C>T) newly occurred in the mature sequence of miR-191-5p seed region in BRCA samples. However, the putative target genes regulated by the miR-191-5p were recognized by the above ten computational programs for the prediction. MACE-Seq outcomes showed that the genes of CDK6(P=0.0001), DAPK1(P=0.02), MTC7(P=0.04), SETD1B(P=0.005), CALN1(P=0.01), and TMOD2(P=0.001) were significantly over-expressed in the BRCA against the NATs. The expression level of the targets was adversely related to the miR-191-5p.